PROSPEK SARJANA NONKEPENDIDIKAN MENJADI PENDIDIK PASCA-KEPUTUSAN MAHKAMAH KONSTITUSI - Rosyid, Moh. (IAIN Pekalongan, 2013)
The existence of educational institutions is determined by the ability of education providers in increasing interest of prospective service users. The character and interest of prospective service users (students) need to be understood by education providers so that prospective students can be accommodated optimally. To know the expectations of service users, this paper describes the efforts of the applicant sued Act No. 14 of 2005 in particular Article 9 which says that the teacher is a qualified bachelor or diploma four. By the plaintiff, ideally requirement is an bachelor of education because it has been equipped with knowledge and skills to educate. Mk’s Decision No. 025 / PUU-IV / 2006 dated February 22, 2007 that are eligible to be a teacher not only bachelor of of education / teacher, but all scholars (S.1) or diploma four (D.4) are qualified to be a teacher. It can be used as the basis that bachelor of non-education should not be pessimistic when it expects educators are largely determined by the expertise of job seekers, not simply print it becomes scholar institutions. The accommodation of undergraduate (bachelor's of any background) become educators is determined by the fulfillment of the requirements to be a teacher and scholar shrewdness carry themselves as self-qualified in the field of science to optimize the network of social interaction.